Strategi Guru Bimbingan Konseling Menyiapkan Siswa dalam Menghadapi Guru Mata Pelajaran yang Kurang Menguasai Pelaksanaan Pembelajaran - Yunita, Yunita; Tambusai, Khairuddin (Continuous Education: Journal of Science and Research, 2025)
This study aims to analyze the strategies of Guidance and Counseling Teachers in helping students deal with subject teachers who do not master or prepare the material at MAN 1 Medan. With a qualitative approach through observation, interviews, and documentation, it was found that the learning process still faces serious obstacles, such as minimal variation in methods, lack of mastery of the material, and limited use of learning media. This causes students to become passive, lose interest in learning, and have difficulty understanding the material. To overcome this, BK Teachers implement various strategies, such as individual and group counseling services, classical guidance, and a persuasive approach to subject teachers. This strategy is effective in increasing students' motivation, mental readiness, and enthusiasm for learning, while creating a more conducive learning environment.